Changing the shape of wool yarns via laccase-mediated grafting of tyrosine - Li, Yu (2021)
The shape of wool yarns was changed by laccase-assisted grafting of tyrosine. Prior to tyrosine grafting a cysteine pre-treatment was optimized aiming to increase the amount of thiol reaction groups available. The best operational conditions for laccase-assisted tyrosine grafting were: i) pre-treatment with cysteine (2.2 mM) in a solution of 20 % ethanol, 15 % propylene glycol and 0.5 % benzyl alcohol, pH=10, 40 °C; ii) tyrosine grafting with 3.0 mM tyrosine, 18 U/mL laccase, pH=5, 40 °C. The shape modification was evaluated by number of curly twists determination on the grafted yarn samples. The thermal and mechanical properties of the grafted wool yarns was evaluated by TGA, DSC and breaking strength determination. The amount of free thiols and weight gain were assessed aiming to infer the role of the cysteine pre-treatment on the final tyrosine grafting and shape modification. The laccase-assisted grafting of tyrosine onto wool yarns have influenced the thermal and mechanical properties of the yarns however without compromising their structural integrity for the final application purposes. The developed methodology to impart new shape to wool yarns is presented herein as an environmentally friendly alternative to chemical methods. The new findings revealed great potentialities for application in similar fibers like hair.